Medicinal Plants of Chamba - Shabnam, Sant Ram (Indian Forester, 1964)
Some of the medicinal plants found in the Chamba district of Himachal Pradesh have been listed after field observations for about three years. The plants have been divided into two groups, namely, (i) Commercially important species, and (ii) Species with local or potential demand. In the case of the former group distribution of species, extent of trade, active principles and uses have been briefly given, whereas in the case of the latter group distribution only based on climatic zones has been indicated with the object of providing a rough guide to those interested in their exploitation.